Pemberdayaan Masyarakat Desa melalui Manajemen Partisipatif: Penelitian - Muhammad Haris; Kiki Kosasih; Agus Rahmatullah; Wawan Lulus Setiawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research explores the role of participatory management in empowering rural communities and its impact on sustainable development. The main focus is directed towards the mechanisms of community involvement in decision-making, program implementation, and village development evaluation. Through a qualitative approach with case studies in several villages in Indonesia, this research shows that the systematic implementation of participatory management can enhance residents' sense of ownership of village programs, strengthen social capital, and produce development that is more responsive to community needs. This research refers to the literature and recent study results, including from Ikopin University, to strengthen the theoretical foundation and analysis.